2009
DOI: 10.1016/j.ceramint.2009.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Fe-mordenite/cordierite monolith for the catalytic decomposition of nitrous oxide

Abstract: Mordenite zeolites were coated on cordierite support by in situ hydrothermal method or dip-coating method. The mordenite/cordierite was characterized by X-ray diffraction (XRD) and scanning electron microscope (SEM) techniques and their stability was studied. The mordenite/ cordierite monolith prepared by in situ synthesis showed much better stability than that prepared by dip-coating. Iron was introduced into mordenite/cordierite by ion exchange and Fe-mordenite/cordierite catalyst was prepared. Fe-mordenite/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…The FeMOR monometallic catalysts (T a and T 60 ) showed about 50% conversion of NO at 300 • C (see Figure 5a,c) which according to the UV-Vis spectra can be attributed to Fe 3+ mononuclear species stabilized in the mordenite framework, similarly to the case of Fe-catalyst for NO x reduction with NH 3 where the active sites are monomeric iron sites (Fe-O-OH at 300 • C) [69]. Other reports also have shown that Fe/zeolites catalysts exhibit high catalytic activity in NO and N 2 O reduction process [70][71][72]. Figure 5b shows the conversion profiles of NO x for bimetallic catalysts prepared at room temperature.…”
Section: Catalytic Conversion Of No With C 3 Hmentioning
confidence: 64%
“…The FeMOR monometallic catalysts (T a and T 60 ) showed about 50% conversion of NO at 300 • C (see Figure 5a,c) which according to the UV-Vis spectra can be attributed to Fe 3+ mononuclear species stabilized in the mordenite framework, similarly to the case of Fe-catalyst for NO x reduction with NH 3 where the active sites are monomeric iron sites (Fe-O-OH at 300 • C) [69]. Other reports also have shown that Fe/zeolites catalysts exhibit high catalytic activity in NO and N 2 O reduction process [70][71][72]. Figure 5b shows the conversion profiles of NO x for bimetallic catalysts prepared at room temperature.…”
Section: Catalytic Conversion Of No With C 3 Hmentioning
confidence: 64%
“…MOR as a type of zeolite has advantages of stability, high proton transport and higher water absorption than methanol or ethanol [24][25][26]. It can also be used in other applications [27]. It was found that there were some pinholes caused by poor compatibility between the Nafion polymer and the zeolite crystals which has been a problem reported in several studies [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 91%
“…[13] One interesting option is to use the unique structure of a parallel-channel monolith (i.e., a continuous body with identical parallel channels), which significantly reduces the common problems associated with conventional adsorbents (i.e., fluidization, high pressure drop, etc.). [14,[18][19][20][21][22][23][24] The second involves the use of hydrothermal synthesis methods such as (i) a direct hydrothermal synthesis (also called in situ growth), or (ii) a secondary growth method, in which the hydrothermal synthesis occurs after seeding the surface of the substrate. Thus, when zeolites thin films are supported on monoliths, one should determine the requirements for the support.…”
Section: Introductionmentioning
confidence: 99%
“…[21] Moreover, comparative studies of both methods (dip-coating versus in situ crystallization) were published for ZSM-5 supported on a metallic honeycomb monolith (FeCr alloy), [22] and for mordenite supported on cordierite monoliths. [23] Regarding the BETA zeolite, only a comparative but not systematic study (dip-coating versus in situ) on cordierite monoliths has been reported by Wang et al [24] In that study, an alumina layer was required to act as a bridge, linking the BETA zeolite and the cordierite monoliths, to improve the mechanical stability. In this sense, to the best of our knowledge, a systematic and detailed comparison between BETA-coated honeycomb monoliths prepared through dip-coating and by using in situ crystallization has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation